The Influence of E-Government on Employee Performance Moderated by Age and Gender (A Study on Employees at Sawahan District, Surabaya City) - Pariyem, Pariyem; Harsono, Soni (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This research aims to explore the impact of the implementation of E-Government on employee performance in the Sawahan District of Surabaya, considering the moderating effects of age and gender. E-Government is regarded as a significant innovation in enhancing the efficiency and transparency of public services. The study employs a quantitative approach, utilising data collection techniques through questionnaires distributed to 100 employees in the Sawahan District. Data analysis is conducted using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The findings of this research conclude that the implementation of E-Government significantly enhances employee performance in the Sawahan District. Age may act as a factor that weakens this influence, whereas gender may serve to strengthen it. Recommendations for future research include expanding the sample size and considering specific training for older employees to improve their adaptation to technology. The limitations of this study include a sample that is confined solely to employees in the Sawahan District, which may not represent the entire population of employees in Surabaya or other regions, as well as an imbalanced proportion of age and gender. It is suggested that future research involve a more diverse sample and implement training programmes for older employees to facilitate better adaptation to the E-Government system.